THE RELATIONSHIP OF ONLINE LEARNING TO THE SOCIAL EMOTIONAL SKILLS OF LASIYAM KINDERGARTEN CHILDREN SURABAYA AGED 5-6 YEARS - Taufiqur Rofiah, Rifka; Hendratno; Hasibuan, Rachma (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
Kindergartens that still require full attention in their learning must adapt to the existing order. This of course reduces all interactions between the teacher and the child directly, resulting in a lack of bonding between the two. This study aims to determine the relationship between online learning and social emotional abilities of Surabaya Kindergarten students aged 5-6 years. This study uses a quantitative approach. The research was conducted at Surabaya's Lasiyam Kindergarten aged 5-6 years. The population of sixty children is taken using non-probability sampling, which means that the selection of the sample is not done subjectively. The type of probability sampling used is simple random sampling chosen by lottery and the formula used to take the sample is the slovin formula, so that in this study a sample of 40 was obtained. Data analysis techniques are interpreted using SPSS. The results show that the significance value is 0.032 <0.05, the significant result is less than 0.05 indicating that the hypothesis is accepted so that it shows a relationship. So it can be concluded that there is a significant relationship between online learning and children's social emotional abilities.